2020
DOI: 10.36740/wlek202006111
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Overweight and Obesity on the Quality Of Life in Children With Bronchial Asthma

Abstract: The aim is to investigate if the overweight (OW) and obesity (OB) impact on the quality of life (QOL) of children with bronchial asthma (BA). Materials and methods: The study included 73 children aged 7 – 17, with moderate BA. Depending on the body mass index, patients were divided into the three clinical groups: normal body weight (NW) – 30 children, OW – 28 children and OB – 15 children. QOL was conducted by the Pediatric Asthma Quality of Life Questionnaire (PAQLQ). The statistical processing was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…In the United States, about 19 per cent of children aged 6–11 are obese, and the proportion of severely obese children was 5.2% ( Hales et al, 2018 ). Asthma is one of the most typical diseases associated with obesity, and among obese children, asthma is also exacerbated and poorly controlled, the quality of life is also reduced, and physical activity is severely inadequate or below the minimum physical activity level ( Okubo et al, 2016 ; Holderness et al, 2017 ; Kupkina et al, 2020 ). Studies have shown that children with asthma have higher BMI and higher rates of obesity than other children ( Glazebrook et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, about 19 per cent of children aged 6–11 are obese, and the proportion of severely obese children was 5.2% ( Hales et al, 2018 ). Asthma is one of the most typical diseases associated with obesity, and among obese children, asthma is also exacerbated and poorly controlled, the quality of life is also reduced, and physical activity is severely inadequate or below the minimum physical activity level ( Okubo et al, 2016 ; Holderness et al, 2017 ; Kupkina et al, 2020 ). Studies have shown that children with asthma have higher BMI and higher rates of obesity than other children ( Glazebrook et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children with asthma have higher BMI and higher rates of obesity than other children ( Glazebrook et al, 2006 ). Having a high BMI can also reduce the quality of life in children with asthma ( Kupkina et al, 2020 ). Our meta-analysis shows that exercise interventions can be effective in reducing BMI in children with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Jakość życia definiowana jest przez tą organizację jako ,,indywidualna percepcja własnej pozycji życiowej z uwzględnieniem warunków kulturowych, systemu wartości w powiązaniu z osobistymi celami, oczekiwaniami, normami, problemami. Wpływa na nią w złożony sposób: zdrowie fizyczne, relacje z innymi ludźmi i ważne dla danej osoby cechy środowiska" [11]. Do badania jakości życia w naukach medycznych i naukach o zdrowiu stosowany jest również wskaźnik jakości życia uwarunkowany stanem zdrowiem (ang.…”
Section: Wprowadzenieunclassified